Isolation and well-being in the time of lockdown - Bourdeau Lepage, Lise; Kotosz, Balázs (REGION, 2021)
In response to the Covid‑19 health crisis, the French government has imposed various measures, referred to as social-distancing measures, including a lockdown with the primary objective of reducing face-to-face interactions between people in order to limit the spread of the virus. This paper seeks to determine if the social-distancing measures and lockdown lead to social isolation for certain people and have an impact on French people’s well-being. First, it reveals that the feelings of social isolation have substantially increased in France during this lockdown. Second, it explores the factors that help to explain these changes by developing a predictive model and reveals that living alone, being a woman, being young are factors that explain this increase in felling of social isolation. Third, the estimation of the effects of changes in feelings of social isolation on changes in the reported level of well-being of French respondents during lockdown shows that people who reported feeling more socially isolated than others has the lowest levels of well-being among the French population; and that the increase in people’s feelings of social isolation during lockdown is a factor that has a negative impact on their level of well-being.